THE IMPACT OF USING TEAM GAME TOURNAMENT TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Royhan Kamal; Hikmah Pravitasari; Siti Ulfa Musyarofah; Reni Asrohillah; Lisda Fauziyah; Wawa Wardiah (English Didactic, 2022)
The aim of this study is to reveal the effectiveness of using Team Game Tournament (TGT) to improve the vocabulary mastery of the second-grade students of Islamic Junior High School in Indonesia. Quantitative method design is used in this research. In order to achieve the objective of this research, the researchers designed a quasi-experimental study. The researchers used two classes to take pre-test and post-test, namely experiment and control classes. The teacher teaches vocabulary mastery in two classes. The experiment class used TGT and the control class used existing English textbook in teaching vocabulary mastery. For the data collection method, this study used vocabulary tests with multiple choice questions based on pictures. The final result of this experiment shows the average value of the experimental class was greater than the control class. Based on the findings, it can be concluded that TGT is effective in improving vocabulary mastery.